From Pramoedya to Ngendon: Interpreting Social Realism and Indonesian Cultural Nationalism from a Distance of Closest Approach - Idayati, Ni Wayan (UPT Pusat Penerbitan LP2MPP ISI Bali, 2025)
This article compares expressions of Indonesian cultural nationalism through two figures from distinct creative mediums: Pramoedya Ananta Toer in literature and I Nyoman Ngendon in the visual arts. Pramoedya, through his novel This Earth of Mankind and his steadfast resolve in voicing social injustice, and Ngendon, through paintings that parallel his role as a guerrilla fighter, both reflect the spirit of social realism amid colonial repression. Their creative practices function as acts of resistance, awakening national consciousness and articulating collective values rooted in the zeitgeist of their time. Drawing on Paul Ricoeur’s hermeneutics, this analysis examines the relationship between narrative, biographical experience, and symbolic representation embedded in their works. The study adopts a framework grounded in the physics concept of distance of closest approach, emphasizing a nuanced reading of the proximity between artwork, social history, and the creative dynamics of both figures. Nationalism and the spirit of nationhood are thus not understood as abstract ideas alone, but as lived, internalized, and embodied experiences manifested through artistic forms within distinct social spheres.